Externally Regulated Specific Molecular Recognition Driven Pathway Selectivity in Supramolecular Polymerization. Issue 44 (17th June 2021) - Chakraborty, Anwesha; Manna, Rabindra Nath; Paul, Ankan; Ghosh, Suhrit
Abstract: This article reveals 4‐dimethylaminopyridine (DMAP) regulated pathway selectivity in the supramolecular polymerization of a naphthalene‐diimide derivative (NDI‐1), appended with a carboxylic acid group. In decane, NDI‐1 produces ill‐defined aggregate (Agg‐1) due to different H‐bonding motifs of the −COOH group. With one mole equivalent DMAP, the NDI‐1/DMAP complex introduces new nucleation condition and exhibits a cooperative supramolecular polymerization producing J‐aggregated fibrillar nanostructure (Agg‐2). With 10 % DMAP and fast cooling (10 K/min), similar nucleation and open chain H‐bonding with the free monomer in an anti‐parallel arrangement produces identical J‐aggregate (Agg‐2a). With 2.5 % DMAP and slow cooling (1 K/min), a distinct nucleation and supramolecular polymerization pathway emerge leading to the thermodynamically controlled Agg‐3 with face‐to‐face stacking and 2D‐morphology. Slow cooling with 5–10 % DMAP produces a mixture of Agg‐2a and Agg‐3. Computational modelling studies provide valuable insights into the internal order and the pathway complexity. Abstract : Externally added 4‐dimethylaminopyridine (DMAP) introduces new nucleation conditions and influences the thermodynamic landscape in the supramolecular polymerization of a carboxylic‐acid appended NDI‐monomer. With 100 % DMAP, well‐defined J‐aggregation results in the formation of fibrillar morphology, irrespective of the cooling rate. With 10 % DMAP, depending on the cooling rate, either J‐aggregate or H‐aggregate (or mixture) is noticed with 1D and 2D morphology, respectively. With 2.5 % DMAP and slow cooling, extended 2D sheet can be obtained from the thermodynamically controlled H‐aggregation.